High-mode vortex-induced vibration of stay cables: monitoring, cause investigation, and mitigation. (28th April 2022) - Kim, Sunjoong; Kim, Sejin; Kim, Ho-Kyung
Highlights: The characteristics of high-mode vortex-induced vibration (VIV) in stay cables were analyzed by applying a new modal decomposition procedure to long-term monitoring data. The shedding frequencies and corresponding critical wind velocities that could induce maximum modal responses produced a constant Strouhal number relationship. By using output-only data, the newly proposed modal damping identification procedure succeeded in identifying the high-mode damping ratios of stay cables. The modal damping estimates of stay cables rapidly decreased toward high-order modes and exhibited an inverse relationship with the relevant VIV amplitudes. The efficacy of Stockbridge dampers in mitigating cable VIVs was examined via field experimentation and comparison analysis. Abstract: Herein is described a case study using long-term field monitoring data from a cable-stayed bridge to investigate the cause of high-mode vortex-induced vibration (VIV) observed in stay cables. Wind characteristics and dynamic responses of girders and stay cables were analyzed to investigate two possible vibration sources–interactions with girders and vortex shedding. To this end, a modal decomposition procedure that included automated peak picking and successive band-pass filtration was proposed. These novel steps revealed a relationship between the shedding frequencies of stay cables and corresponding critical wind velocities. The main cause of large-amplitude VIVs was diagnosed using a novel damping identification procedure that consisted of automated modal decomposition, temporal correlation, and optimization-based curve fitting techniques. The damping identification results demonstrated how the modal VIV amplitudes of stay cables have a strong dependency on damping capacity. The effectiveness of Stockbridge dampers in mitigating high-mode cable VIVs was subsequently examined through field application and comparison analysis during a typhoon. The unique interaction between stay cable vibrations and the buffeting response of bridge girders observed during this period was additionally discussed.